The effects of nuclear level density model and alpha optical model potential to the excitation functions of novel therapeutic radionuclides - Ahmad Kamal, Nur Najwa; Nizam, Syafie; Abdul Aziz, Azni (Elsevier Ltd, 2024)
In this study, the theoretical cross sections of 209Bi(α,2n)211At, 65Cu(α,n)68Ga, 100Ru(α,n)103Pd, and 121Sb(α,n)124I are calculated using TALYS 1.96, incorporating the effects of the alpha optical model potential and nuclear level density models. The validation process involves comparing the calculated cross sections with experimental data and utilizing statistical deviation factors. This comparison allows us to determine the optimal combination of nuclear model parameters for each reaction. The result shows that theoretical calculations which utilized semi microscopic level density models and alpha OMP managed to describe the excitation functions close to the experimental data. The comparison of nuclear model calculations with experimental data plays a crucial role in ensuring the reliability of the data, making it an essential aspect of modern evaluation procedures